Analisis Kualitas Pelayanan Menggunakan Metode Service Quality (Servqual): Studi Kasus Prima Freshmart SV IPB - Hamdah Istifha Dinia; Haniyyah Laura Balqis; Wilman Aprilian Nurrahman; Merin Ananda; Nurul Nabila; Khoirul Aziz Husyairi; Tina Nur Ainun (Jurnal Manajemen Bisnis Era Digital, 2024)
Service Quality is fulfilling customer needs by offering products and services that exceed customer expectations, so that they can satisfy customer desires. Prima Freshmart, which is the object of this research, is a retail store that plays a crucial role in meeting people's needs. The aim of this research is to evaluate the level of customer satisfaction with the services provided at Prima Freshmart. The method used is the Service Quality Method (Servqual), this method can identify the service criteria expected by customers. Research on 97 respondents at Prima Freshmart SV IPB showed valid values ​​in measuring service levels. The results of analysis using Servqual show an average gap of -0.175. The attribute that has the biggest gap is being fast in providing promo information, so there is a need to improve in providing promo information quickly to customers.